Use Of Pleasure / Michel Foucault ; translated - "Foucault, Michel." (New York, 1985)
The Volume II: the use of pleasure, his first book to appear posthumously, we can appreciate the stature of this intellectual achievement and see how much Foucault accomplished before his untimely death in June 1984
Keywords: Sex (Psychology).